A Comparison of Functional Features of Chinese and US Mobile Apps for Pregnancy and Postnatal Care: A Systematic App Store Search and Content Analysis - Hongli Yu; Hongli Yu; Juan He; Xinghao Wang; Weilin Yang; Bo Sun; Anna Szumilewicz (Frontiers Media S.A., 2022)
BackgroundPregnancy to postpartum (PtP) applications (apps) are becoming more common tools to document everything from pregnancy and delivery to nutrient allocation, life taboos, and infant medical examinations. However, the dependability, quality, and efficacy of these apps remain unclear. This study examined the features and functions of mobile PtP care apps accessible in China and the United States and to identify the major gaps that need to be addressed.MethodsApps were selected by searching the Apple App Store and Android Markets (in the US and China) for the terms "pregnancy" and "postpartum" in Chinese and English. The apps' security, quality, and effectiveness were investigated, and chi-square tests and analysis of variance were performed to examine the differences in characteristics between apps available in the US and China.ResultsA total of 84 mobile PtP care apps (45 from the US and 39 from China) were included. A total of 89.7% (35/39) of Chinese mobile apps did not provide safety statements or supporting evidence. The objective app quality ratings for Chinese and US apps were 3.20 ± 0.48 (mean ± standard deviation) and 3.56 ± 0.45, respectively (p > 0.05). A greater number of Chinese apps provided app-based monitoring functions, namely recording fetal size (n = 18, 46.2% in China vs. n = 3, 6.7% in the US), contractions (n = 11, 28.2% in China vs. n = 0, 0% in the US), pregnancy weight (n = 11, 28.2% in China vs. 0, 0% in the US), and pregnancy check-up reminders (n = 10, 25.6% in China vs. n = 0, 0% in the US). Meanwhile, a greater number of US apps provided exercise modules, namely pregnancy yoga (n = 2, 5.1% in China vs. n = 21, 46.7% in the US), pregnancy workouts (n = 2, 5.1% in China vs. n = 13, 28.9% in the US), and pregnancy meditation (n = 0, 0% in China vs. 10, 22.2% in the US) (p < 0.01). A medium security risk was identified for 40% (18/45) of apps in the US and 82.1% (32/39) of apps in China (p < 0.01).ConclusionsThe functionality and characteristics of in-store mobile apps for PtP care varied between China and the US. Both countries' apps, particularly Chinese apps, encountered issues related to a lack of evidence-based information, acceptable content risk, and program evaluations. Both countries' apps lacked proper mental health care functions. The findings suggest that the design of app features should be enhanced in both countries, and increased interaction between app creators and users is recommended.